ChemInform Abstract: A New Water Oxidation Catalyst: Lithium Manganese Pyrophosphate with Tunable Mn Valency. Issue 28 (15th July 2014) - Kang, Kisuk; et al., et al.
Abstract Inductively coupled plasma mass spectrometry, XPS, XANES, galvanostatic charging—discharging, and cyclic voltammetry analysis indicate that Li2‐xMnP2O7 (x = 0.3, 0.5, 1) exhibits high catalytic stability for water oxidation without additional delithiation or phase transformation.